Development of Aswaja Learning Modules to Strengthen Religious Moderation in School Learning - Zahrotul Muzdalifah; Umi Salamah; Siti Mutholingah; Faris Khoirul Anam; M. Alifudin Ikhsan (Universitas Al-Amien Prenduan, 2025)
Strengthening the values of religious moderation in schools requires teaching materials that are relevant, systematic, and easily understood by students. At Darul Faqih Indonesia Junior High School, the Aswaja teaching materials currently in use have not fully addressed students’ learning needs, indicating the necessity for more innovative and engaging learning resources. This study aims to develop a valid Aswaja learning module that supports the learning process and strengthens moderate religious values. The research employed a research and development (R&D) approach using a modified ADDIE model. Data were collected through interviews and questionnaires and analyzed using qualitative and quantitative descriptive techniques. The resulting product is an Aswaja learning module designed to integrate religious moderation values, 21st-century learning principles, and technology-based instructional media. Validation results demonstrate a very high level of feasibility, with scores of 93% from subject matter experts, 92.92% from media experts, and 98.40% from learning experts. These findings indicate that the developed module effectively meets learning objectives and indicators while supporting adaptive, interactive, and student-centered learning. Practically, the module serves as a structured and applicable learning resource that assists teachers in implementing Aswaja learning integrated with religious moderation values and encourages students’ active and independent learning. Theoretically, this study contributes a development model for Aswaja teaching materials aligned with religious moderation and 21st-century, technology-based learning, which may inform similar educational developments in other contexts.